COVID-19, conservation, and tourism in Namibia’s conservancies: Socioeconomic and land-use impacts - Gargallo, E.; Heita, J. (Conservation, land conflicts, and sustainable tourism in Southern Africa: Contemporary issues and approaches, 2022)
Since the 1990s, many African countries, in collaboration with international institutions, have developed a diversity of so-called Community Conservation (CC) programmes that are supposed to enhance the power of local communities over wildlife and forests, as well as to increase the revenue accruing to these populations from conservation-related economic activities. Most of these programmes are based on the premise that tourism will provide income and jobs to be distributed among local community members and this will increase their support for wildlife conservation. Namibia’s programme of Communal Conservancies has been depicted as one of the most successful in Africa and is often implemented through tourism business joint ventures between communities and private companies. One of the main effects of COVID-19 and its preventive measures though, has been an almost total collapse of international tourist visits to Namibia, leading to a sharp fall in income to Conservancies and communities. Through the analysis of both the general evolution of Conservancies and of two specific cases, this chapter analyses how the crisis in the tourism sector has impacted populations in Conservancy areas. Special focus will be placed on three issues: the socio-economic impact of declining revenues and employment on the population, the effects on wildlife behaviour and human-wildlife conflict, and, finally, the possible changes in land use in Conservancies. Although our data is still preliminary, it already suggests what may happen to community wildlife conservation schemes when tourism-generated income vanishes, and the way land use and agropastoralism may evolve when conservation loses ground.